What can onto-epistemology reveal about Holocaust education? The case of audio-headsets at Auschwitz-Birkenau State Museum. Issue 3 (3rd July 2018) - Henderson, Susan; Dombrowski, Lindsay
ABSTRACT: This article adopts onto-epistemological framework for investigating pedagogical practices, focusing on the specific context of Holocaust education excursions to Auschwitz-Birkenau State Museum (ABSM) and focusing on pedagogy in and through audio-headsets. It is based on an extensive dataset collected through ethnographic-inspired observations at ABSM, and focusing particularly upon three school-based excursion groups (two Scottish, one Norwegian). Through processes of spatial ordering and intra-action, we argue that the relationships comprising 'things' (e.g. students, exhibitions in the Museum, knowledges about the Holocaust) can be explored as more-and-less visible.